Horizontal arrangements: strategy for reducing the asymmetry information for dairy farmers in Paraná, Brazil - Marcel Moreira de Brito; Ferenc Istvan Bánkuti; Sandra Mara Schiavi Bánkuti; Maria Clara Melo Ferreira; Júlio César Damasceno; Geraldo Tadeu dos Santos; Maximiliane Alavarse Zambom (Ciência Rural, 2015)
An empirical investigation was conducted to study whether dairy farmers involved in horizontal arrangements (HA) have lower information asymmetry than those who do not participate in HA. Our assumption is that greater access to information results in fewer risky decisions in production systems. One hundred and twenty semi-structured questionnaires were applied to dairy farmers located in four different geographical regions in Paraná State, Brazil. Exploratory factor analysis was used to define factors related to information asymmetry in dairy agribusiness system (DAS) and four factors were defined. In a second step, the 120 dairy farmers were split into two groups: the first one involved in HA and the second one not involved in HA. Mean test (t-student) were performed to compare these groups between factors. Significant differences (P<0.05) were observed for factors related to transaction information and for general market information, and dairy farmers participating in HA achieved the greatest values. Finally, it can be concluded that dairy farmers who participate in HA have higher access to information, which can create an environment with lower information asymmetry and, consequently, be subject to lower risks than dairy farmers who do not participate in HA